Endoscopic Treatment of Gastric Bezoars: A Report of Three Cases - Younghee Choe; Joon Sung Kim; Byung-Wook Kim (Yong Chan Lee, 2024)
Bezoars, including phytobezoars, trichobezoars, and pharmacobezoars, are accumulations of undigested substances in the gastrointestinal tract. We report three cases of gastric bezoars. Case 1: An 86-year-old woman presented with a one-month history of abdominal pain and vomiting. Esophagogastroduodenoscopy revealed gastric bezoars; consumption of 2 L of cola daily for 2 weeks resulted in complete disappearance of the bezoars. Case 2: An asymptomatic 63-year-old woman underwent esophagogastroduodenoscopy, which revealed a gastric bezoar. Cola spraying and endoscopic lithotomy were ineffective; therefore, the patient underwent laparoscopic removal of the bezoar for management of small bowel obstruction secondary to the bezoar fragments. Case 3: A 6-year-old girl with a history of pica underwent two laparoscopic surgeries 10 months apart for recurrent trichobezoars. We report our treatment approach in three patients who presented with gastric bezoars.